BLENDED LEARNING AS A FUTURE LEARNING MODEL TO ENHANCE STUDENTS’ LEARNING COMPETENCE - Mantra Ida Bagus Nyoman (Journal on Studies in English Language Teaching (JOSELT), 2021)
The trend of blended learning as a learning model has increased dramatically since the outbreak of Covid-19. This library study was intended to explore the usefulness of blended learning to promote students' learning. The data were collected from various sources including online sources. This study revealed that blended learning is a learning process that utilizes various approaches. The learning process takes place conventionally and online. The blended learning model can be used to improve student learning competence because students do not only listen to teachers’ lectures but also do more learning activities such as observing, undertaking, presenting, creating, transferring, and so on. In blended learning, students have positioned themselves as active learners so that students' attention and learning outcomes increase. Moreover, in blended learning, it is very possible for learning interactions to occur from anywhere and anytime. In the application of blended learning, educators should ensure that all students have adequate facilities and infrastructure in order to make the learning process becomes successful.